2023
DOI: 10.1088/1361-6579/aca0d9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular autonomic modulation during passive heating protocols: a systematic review

Abstract: Objective: To conduct a systematic review about the possible effects of passive heating protocols on cardiovascular autonomic control in healthy individuals. Approach: The studies were obtained from MEDLINE (PubMed), LILACS (BVS), EUROPE PMC (PMC) and SCOPUS databases, simultaneously. Studies were considered eligible if they employed passive heating protocols and investigated the cardiovascular autonomic control by spontaneous methods, such as heart rate variability (HRV), systolic blood pressure variability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…One of the main determinants of baroreceptor function is the activity of the autonomic nervous system (ANS), which, upon postural baroreceptor unloading, elicits adjustments in sympathetic and parasympathetic outflow to the cardiovascular system, increasing both the heart rate and vasoconstriction [ 38 , 39 , 40 , 41 ]. Our previous study suggested the presence of ANS disturbances in cardiovascular regulation in patients with PAF, as evidenced by diminished heart rate variability during HUT [ 30 ] together with the delay in the baroreflex activation immediately after tilting up, as shown in Figure 2 .…”
Section: Discussionmentioning
confidence: 99%
“…One of the main determinants of baroreceptor function is the activity of the autonomic nervous system (ANS), which, upon postural baroreceptor unloading, elicits adjustments in sympathetic and parasympathetic outflow to the cardiovascular system, increasing both the heart rate and vasoconstriction [ 38 , 39 , 40 , 41 ]. Our previous study suggested the presence of ANS disturbances in cardiovascular regulation in patients with PAF, as evidenced by diminished heart rate variability during HUT [ 30 ] together with the delay in the baroreflex activation immediately after tilting up, as shown in Figure 2 .…”
Section: Discussionmentioning
confidence: 99%